2020
DOI: 10.1088/1361-648x/ab884a
|View full text |Cite
|
Sign up to set email alerts
|

Nonlocal density functional theory of water taking into account many-body dipole correlations: binodal and surface tension of ‘liquid–vapour’ interface

Abstract: In this paper we formulate a nonlocal density functional theory of inhomogeneous water. We model a water molecule as a couple of oppositely charged sites. The negatively charged sites interact with each other through the Lennard–Jones potential (steric and dispersion interactions), square-well potential (short-range specific interactions due to electron charge transfer), and Coulomb potential, whereas the positively charged sites interact with all types of sites by applying the Coulomb potential only. Taking i… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
31
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(31 citation statements)
references
References 62 publications
0
31
0
Order By: Relevance
“…Many studies on dense uniform liquids have demonstrated the dominant role of shortranged harshly repulsive intermolecular forces in determining structural correlations, which provides the insight that attractive intermolecular forces essentially cancel due to the symmetric configurations of molecules in uniform liquids [1][2][3]. In contrast, translational invariance of molecular arrangements is broken in non-uniform liquids [4][5][6][7][8][9][10][11][12]. Accordingly, both attractive and repulsive forces can, for instance, significantly influence the structure of a Lennard-Jones (LJ) fluid next to a hard wall because the vector sums of the long-range attractive forces do not cancel each other.…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…Many studies on dense uniform liquids have demonstrated the dominant role of shortranged harshly repulsive intermolecular forces in determining structural correlations, which provides the insight that attractive intermolecular forces essentially cancel due to the symmetric configurations of molecules in uniform liquids [1][2][3]. In contrast, translational invariance of molecular arrangements is broken in non-uniform liquids [4][5][6][7][8][9][10][11][12]. Accordingly, both attractive and repulsive forces can, for instance, significantly influence the structure of a Lennard-Jones (LJ) fluid next to a hard wall because the vector sums of the long-range attractive forces do not cancel each other.…”
Section: Introductionmentioning
confidence: 99%
“…There are several situations in which such non-uniform states of liquid molecules emerge. Inhomogeneities occur [4][5][6][7][8][9][10][11][12]: (i) at interfaces between liquid-gas, liquid-liquid, and liquid-crystal phases; (ii) in the adsorption of liquids at solid substrates or walls; (iii) for fluids in confining geometries, such as slits and pores; and (iv) in the sedimentation equilibrium of colloidal particles under gravity. Theoretically, a non-uniform state can be created by adding an interaction potential term associated with an external field.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations